Kelayakan Usaha Madu Berbasis Eduwisata Lebah Tanpa Sengat Di Pondok Pesantren Kabupaten Lebong - Rita Nurmalina; Nia Rosiana; Akso Diana (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2024)
The Nurul Qur'an Islamic boarding school in Lebong Regency has a stingless bee educational tour to provide education on bees and honey as a promotion to visitors. This research aims to (1) determine the feasibility of a honey business with an edutourism concept at the Nurul Qur'an Islamic Boarding School from a non-financial perspective (2) measure the financial feasibility of a honey business with an edutourism concept without training packages and homestays compared with the presence of training packages and homestays using NPV, Net B/C, IRR, and Payback Period as tools for measuring investment criteria (3) measure the level of sensitivity to changes in maximum production, input and output prices of honey with the edutourism concept without training packages and homestays compared with the presence of training packages and homestays that can be accepted by the perpetrator business. Data collection methods include surveys, interviews and document studies, the sampling technique uses purposive sampling. The results of the analysis of non-financial aspects which include market aspects, technical aspects, management and legal aspects, social and economic aspects, and environmental aspects show that this business is feasible to run. The results of the financial analysis seen from the Payback Period, IRR, NPV and Net B/C calculations show that scenario 2 is more profitable than scenario 1. The results of sensitivity analysis using switching values ​​for scenarios 1 and 2 on input components are more sensitive to product prices and a decrease in honey production, Meanwhile, the output component is more sensitive to labor costs, so it is recommended to maintain product availability and quality and improve marketing with various effective approaches